Mountains for Preliminary Division of Mass by Fraction Coefficients - G. K., Payziev; M. B., Saidyusupov (American Journal of Biodiversity, 2026)
The article presents the process of separating crop yield components based on the difference in their friction coefficients, particularly during the harvest of potatoes by potato harvesters. At the same time, components with a large friction coefficient will be carried out by the ridge, and components with a small friction coefficient will be rolled out of it. Therefore, hills are used to separate small plant impurities.